Tota Lake Pollution and Biological Models for Genotoxicity Studies (2020)
Tota Lake is a water source of great importance at a regional and national level given its environmental and economic value, the latter represented by agricultural, livestock and fish farming activities. These activities have contributed to the contamination observed at present, being an environmental problem in constant rise, where the health, the development of the communities and the ecological processes have been affected. In fact, Lake Tota has been classified as one of the most threatened ecosystems on the planet by the global network of wetlands. Despite the environmental problems posed by the contamination of the Lake, there are very few studies that investigate the genetic damage generated by exposure to the toxic agents present in this basin. In this regard, an optimal biological model for genotoxicity studies is the zebrafish, given its high genetic homology with humans, as well as its capacity for regeneration, adaptation and immune response to high concentrations of chemical compounds such as pesticides. This review focuses on recent reports on Tota Lake contamination and the use of biological models for genotoxicity studies.